Weak Compactness of Almost Limited Operators - Aziz Elbour; Nabil Machrafi; Mohammed Moussa (Journal of Function Spaces)
This paper is devoted to the relationship between almost limited operators and weakly compact operators. We show that if F is a σ-Dedekind complete Banach lattice, then every almost limited operator T:E→F is weakly compact if and only if E is reflexive or the norm of F is order continuous. Also, we show that if E is a σ-Dedekind complete Banach lattice, then the square of every positive almost limited operator T:E→E is weakly compact if and only if the norm of E is order continuous.